Empirical evaluation of ethical practices and digitalization of agricultural system with the mediation of user behavior: A case study of Pakistan - Manzoor, Faiza; Wei, Longbao; Chen, Jingyuan (Frontiers in Environmental Science, 2023)
Pakistan is one developing country and 70% of the population is depending on Agriculture and faces a lack of innovation in the agriculture sector overall. the main objectives of our study were to (i) identify ethical practices (knowledge-sharing, trustworthiness in loan providing, loyalty in professionalism, responsibility of actions, and accountability) of the agriculture departments and institutions or government towards improving digital technology in the agriculture sector. (ii) Quantify user behavior in the digitalization of the agricultural system. (iii) Identify the intervening role of user behavior in relation to ethical practices and agricultural technology development. The study examined 490 users of farming technologies who work in the agriculture sector in two provinces of Pakistan. Using the Baron and Kenny framework, this research confirmed the prediction that user behavior mediated the relationship between ethical practices and agricultural technology in a four-step process. The main outcomes of the study have revealed a positive and significant impact of ethical practices on the development of the digitalization of the agricultural system. Specifically, the study indicated that “user behavior” significantly mediates the association between ethical practices and agricultural technology development. Furthermore, this study proposes that it is essential for Pakistan's agriculture sector to nurture circumstances dedicated to better practices as it will not only attract more residents to agricultural growth but also help the agriculture sector achieve its eventual goal of increased productivity.